Equivalence of human and bovine dentin matrix molecules for dental pulp regeneration: proteomic analysis and biological function. (November 2020) - Horsophonphong, Sivaporn; Sercia, Ashley; França, Cristiane M.; Tahayeri, Anthony; Reddy, Ashok P.; Wilmarth, Phillip A.; Surarit, Rudee; Smith, Anthony J.; Ferracane, Jack L.; Bertassoni, Luiz E.
Highlights: Bovine dentin contains active molecules with similar biological function to human Dentin matrix from both species stimulated regenerative processes of dental pulp Bovine dentin could be a human dentin substitute for dental pulp regeneration Abstract: Objective: To compare proteomics and biological function of human dentin matrix molecules (hDMMs) and bovine dentin matrix molecules (bDMMs). Design: Dentin powder from human or bovine teeth (n = 4) was demineralized in 10% (v/v) ethylenediaminetetraacetic acid for 7 days. The extracts were dialyzed, lyophilized and proteins were characterized using liquid chromatography-tandem mass spectrometry and shotgun proteomic analysis. To study biological function, mouse-derived undifferentiated dental pulp cells (OD21) were treated with 0.01, 0.1 or 1 μg/mL of hDMMs or bDMMs and proliferation was measured after 24 hours and 48 hours using 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Cell migration was assessed after 24 hours using a Boyden chamber. Alizarin Red S staining was used to evaluate mineral formation. Results: There were 307 proteins identified, of which 93 proteins were common to both species. Gene Ontology functional analysis demonstrated similar pattern of biological process in both species which consisted mainly of tissue development and biomineralization. hDMMs and bDMMs both enhanced cell proliferation. After 24 hours, all concentrations of bDMMs promoted cell proliferation ( p ≤ 0.05), while hDMMs did not affect proliferation. After 48 hours, groups with 1μg/mL of bDMMs and 0.01μg/mL of hDMMs had increased cell proliferation compared to control ( p ≤ 0.0001). All concentrations of hDMMs and bDMMs enhanced cell migration and mineralization ( p ≤ 0.0001). Conclusion: bDMMs has similar biological functions as hDMMs. Moreover, bDMMs stimulated cell proliferation, migration and differentiation similar to hDMMs.